Global Food Waste on Circular Economy and Knowledge Co-Production - Rana Qonita Rofila (Journal of World Trade Studies, 2022)
The food waste issue and the circular economy collaborate as an alternative solution for both the economy and the environment. Knowledge co-production can help to explain more about this issue. These approaches make the value of waste change into something beneficial to the economy. Many institutions, agendas, agreements, and civil movements established and caused the politics of waste to become a fruitful discourse. Transitioning to the circular economy that includes social, political, and even technological changes can be challenging or a good solution for some nations. Every actor has an important role and requires good cooperation for transitioning to the circular economy while tackling the food waste issue.